Analisis Konsep Green Marketing pada Bank Syariah - Elfa Duwina; Muhammad Iqbal Fasa (Yayasan Literasi Sains Indonesia, 2024)
This study investigates the concept of green marketing in Islamic banking, exploring its principles, challenges, and opportunities for implementation. Employing a combination of qualitative and quantitative research methods, including interviews with Islamic banking experts and a survey of consumers, the study identifies key Islamic principles that underpin green marketing practices. These principles include maṣlaḥah (public interest), istiqlāl (sustainability), and adāl (justice). The research reveals that while awareness of environmental issues is increasing, Islamic banks face challenges in adopting green marketing practices, such as limited incentives, a lack of clear standards, and high initial costs. However, opportunities exist to leverage green marketing as a competitive advantage, attract environmentally conscious customers, and contribute to sustainable development. The study concludes that promoting green marketing in Islamic banking necessitates a collaborative effort involving government, regulatory bodies, and Islamic banks themselves. Specific examples of green marketing practices in Islamic banking identified in the study include offering financing for environmentally friendly businesses, promoting online banking to reduce paper consumption, and developing green deposit programs. The findings suggest that by integrating Islamic principles and addressing the challenges, Islamic banks can effectively implement green marketing strategies to achieve both financial and environmental sustainability.